PREDIKSI LABA MASA DEPAN MELALUI PERSISTENSI LABA DENGAN ARUS KAS OPERASI DAN AKRUAL - Marvella, Audrys; Imelda, Elsa; Simina, Juni (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to determine the effect of operating cash flow and accruals on earning predictability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2018. This research used 150 samples from selected manufacturing companies with purposive sampling method. The analysis technique used in this research is multiple linear regression, which performed classical assumption in advance, before testing the hypothesis. The data in this research were inputted and calculated using Microsoft Excel program and processed using the EViews 12.0 program. The results of this study indicate that the operating cash flow had a positive and significant effect on earning predictability, and accruals had a positive and significant effect on earning predictability.